Insights into chloroplast genome structure and phylogenetic relationships within the Sesamum species complex (Pedaliaceae) - Zoclanclounon, Yedomon Ange Bovys; Thamilarasan, Senthil Kumar; Mo, Youngjun; Ahn, Byoung-Ohg; Kim, Jeong-Gu; Lee, Keunpyo (Frontiers in Genetics, 2023)
In Sesamum species complex, the lack of wild species genomic resources hinders the evolutionary comprehension of the phylogenetic relationships. In the present study, we generated complete chloroplast genomes of six wild relatives (Sesamum alatum, S. angolense, S. pedaloides, Ceratotheca sesamoides (syn. S. sesamoides), C. triloba (syn. S. trilobum), S. radiatum and a Korean cultivar S. indicum cv. Goenbaek. A typical quadripartite chloroplast structure including two inverted repeats (IR), a large single copy and a small single copy, was observed. A total of 114 unique genes encompassing 80 coding-genes, four ribosomal RNAs, and 30 tranfer RNAs were counted. The chloroplast genomes (152,863-153,338 bp) exhibited IR contraction/expansion phenomenon and were quite conserved in both coding and non-coding regions. However, high values of nucleotide diversity index were found in several genes including ndhA, ndhE, ndhF, ycf1, and psaC-ndhD genes. Concordant tree topologies suggest ndhF as a useful marker for taxon discrimination. The phylogenetic inference and the time divergence dating indicates that S. radiatum (2n = 64) have occurred concomitantly with the sister species C. sesamoides (2n = 32) about 0.05 million years ago (Mya). Besides, S. alatum was clearly discriminated by forming a single clade, showing its long genetic distance and potential early speciation event in regards to the others. Altogether, we propose to rename C. sesamoides and C. triloba as S. sesamoides and S. trilobum respectively, as suggested earlier based on morphological description. This study provides the first insight into the phylogenetic relationships among the cultivated and wild African native relatives. The chloroplast genomes data lay a foundation for speciation genomics in Sesamum species complex.